Bij het 40-jarig jubileum. Plaats personen op achterzijde. Afdruk van exemplaar van Gemeentearchief Arnhem
Bij het 40-jarig jubileum. Plaats personen op achterzijde. Afdruk van exemplaar van Gemeentearchief Arnhem.